Uncovering Islamic Economic Systems in Pesantren: a Systematic Review Across Indonesia, Thailand, and Bangladesh - Moh. Kusno; Nur Azizah; Ach. Puniman (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2026)
This study departs from the tendency to view pesantren solely as an educational institution, while its economic dimension is rarely understood as an inherent system. The research aims to identify and synthesize repeated economic patterns in pesantren studies through Systematic Literature Review in three contexts: Indonesia, Thailand, and Bangladesh. The key question is whether the economic practice shows consistent characteristics so that it can be understood as an Islamic economic system inherent in the structure of Islamic boarding schools. The SLR method follows the PRISMA flow by examining 41 selected articles. The results showed consistent patterns: maqāṣid foundations, spiritual leadership, experiential entrepreneurial pedagogy, formal business institutions, Islamic social finance financing, community empowerment orientation, and institutional adaptive capacity. This cross-context consistency emphasizes that the economy is not an additional element, but rather the structural foundation of the Islamic boarding school. The study's main contribution is the ontological redefinition of pesantren as an Islamic value-based economic system, while offering a new analytical framework for the study of pesantren studies, Islamic economics, and community-based education